A comparative analysis of the main characteristics of human capital in Bulgaria and Russia - P. D. Shishmanova (Российский технологический журнал, 2020)
Human capital is one of the main factors in the development of the modern economy. Its condition and trends are determined by the specific conditions in each country. The purpose of this report is to examine the extent to which the different political and socio-economic conditions in Bulgaria and Russia affect the main characteristics of human capital. The analysis of the state of human capital is presented in quantitative and qualitative aspect. Quantitative characteristics are mainly related to changes in the population, its age structure and the state of its health. The educational level of the population and the quality of the educational training are considered in a qualitative aspect. The comparative analysis shows that Bulgaria and Russia have many similarities regarding the state and development of human capital, but the differences prevail. In Bulgaria, the population, as well as labor resources, are rapidly declining, and in Russia the changes are in a positive direction. Russia still manages to maintain a good quality of education, and Bulgaria is retreating from its good positions. On this basis, it is concluded that the different political and economic conditions in the two countries form a specific profile of their human capital, but generate similar problems. This imposes the need for rapid and effective measures aimed at modernizing education and health care systems, changing the funding model and its results, as well as adapting external models and policies to national specifics and traditions.